Acute drug transfer and particle release of drug coated balloons within a porcine in-vitro model - Brandt-Wunderlich Christoph; Almstädt Lucas; Kaule Sebastian; Reske Thomas; Schmidt Wolfram; Schmitz Klaus-Peter; Grabow Niels (Current Directions in Biomedical Engineering, 2017)
Drug coated balloons (DCB) are used in the therapy of coronary as well as peripheral artery disease. The success of drug transfer to the vessel wall depends on the excipient used in combination with paclitaxel as antiproliferative drug. Although in-vivo studies show very good results with this technology, there is a lack of in-vitro test methods for characterization of various DCB available on the market. This study describes a method to gain information about the drug transfer and the particle release of three different DCB based on cetylpyridinium salycate (Cetpyrsal), hyaluronic acid and iopromide within a porcine in-vitro model. The Cetpyrsal-based DCB showed promising results with the highest drug transfer while producing the lowest number of particles.